Posted by **Tifini** on Tuesday, July 10, 2012 at 1:07pm.

Let f(x)=-16x^2-x^3 and g(x)=-2-4x^2. Then f(x)-g(x) equals____?

A. 1-2x^2-x^3

B. -1-2x^2+x^3

C. 1+2x^2-x^3

D. -1+2x^2+x^3

## Answer This Question

## Related Questions

- Integrated Math 1 - Let f(x)=-16x^2-x^3 and g(x)=-2-4x^2. Then f(x)-g(x) ...
- Integrated Math 1 - Let f(x)=x^1999 and g(x)=2x-x^5. Then f(x)g(x) equals____? A...
- Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...
- algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...
- math - please help - Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - ...
- Math - 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10...
- algebra - x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem ...
- Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...
- math - The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct? [(2x...
- Math - Which of the following expressions is equivalent to (-2x^5 y^2)^4 A. -16x...

More Related Questions